Genomic Architecture of AP2/ERF Superfamily Genes in Marigold (Tagetes erecta) and Insights into the Differential Expression Patterns of AP2 Family Genes During Floral Organ Specification - Hang Li; Guoqing Chen; Shirui Hu; Cuicui Liu; Manzhu Bao; Yanhong He (Agronomy)
The APETALA2/Ethylene-Responsive Factor (AP2/ERF) superfamily is one of the largest transcription factor families in plants, playing diverse roles in development, stress response, and metabolic regulation. Despite their ecological and economic importance, AP2/ERF genes remain uncharacterized in marigold (Tagetes erecta), a valuable ornamental and medicinal plant in the Asteraceae family known for its unique capitulum-type inflorescence with distinct ray and disc florets. Here, we conducted a comprehensive genome-wide analysis of the AP2/ERF superfamily in marigold and identified 177 AP2/ERF genes distributed across 11 of the 12 chromosomes. Phylogenetic analysis revealed their classification into the AP2 (28 genes), ERF (143 genes), RAV (4 genes), and Soloist (2 genes) families based on domain architecture. Gene structure and motif composition analyses demonstrated group-specific patterns that correlated with their evolutionary relationships. Chromosome mapping and synteny analyses revealed that segmental duplications significantly contributed to AP2/ERF superfamily gene expansion in marigold, with extensive collinearity observed between marigold and other species. Expression profiling across different tissues and developmental stages indicated distinct spatio-temporal expression patterns, with several genes exhibiting tissue-specific expression in Asteraceae-specific structures. In floral organs, TeAP2/ERF145 exhibited significantly higher expression in ray floret corollas compared to disc florets, while TeAP2/ERF103 showed stamen-specific expression in disc florets. Protein interaction network analysis revealed AP2 as a central hub with extensive predicted interactions with MADS-box and TCP family proteins. These findings suggest that AP2 family genes may collaborate with MADS-box and CYC2 genes in regulating the characteristic floral architecture of marigold, establishing a foundation for future functional studies and molecular breeding efforts to enhance ornamental and agricultural traits in this economically important plant.